Ethephon effect on defoliation of cluster zone, Botrytis bunch rot, and viticultural performance of ‘Cabernet Sauvignon’ grapevine in highland region of southern Brazil Efeito do Ethephon na desfolha da zona de cacho, podridão cinzenta de cachos e desempenho vitícola da uva ‘Cabernet Sauvignon’ em região serrana do sul do Brasil - Furini G.* (2024)
© 2024, Universidade Federal de Santa Maria. All rights reserved.Phytoregulators have been used as grapevine defoliants in cluster zones to manage and improve grape quality and production. The present study evaluated the effect of the phytoregulator ethephon on the grapevine defoliation of the cluster region, Botrytis bunch rot (BBR) epidemiology, and the viticultural performance of ‘Cabernet Sauvignon’, during the 2018/2019 and 2019/2020 growing seasons, in the highland region of the Santa Catarina State, Southern Brazil. Ethephon was applied in the bunch region of both sides of the grapevine vegetative canopy, at the phenological stage of beginning of ripening (BBCH-81) in five active ingredient doses (0 mg L-1 (control); 720 mg L-1; 1,440 mg L-1; 2,160 mg L-1; and 2,880 mg L-1), following a randomized block design with four replications and five plants per replication. The following parameters were evaluated: BBR epidemiology, vegetative, productive, and technological and phenolic maturation. The increasing ethephon doses significantly reduced the linear leaf drop and affected the technological and phenolic grape maturation parameters, improving the must pH, total polyphenols, color 420, 520, and 620 m, color intensity (°hue angle), and anthocyanin, and reducing the total solubre solids in the ‘Cabernet Sauvignon’ grapevine. However, this significant effect on the linear leaf drop and the technological and phenolic maturation parameters did not interfere with other vegetative, productive, and BBR epidemiology parameters evaluated in the edaphoclimatic conditions of the highland region of southern Brazil.